(untitled) (Bangladesh Journal of Pharmacology, 2015)
Despite advances in conventional therapies, treatment of prostate cancer is still a challenge. The study aims to assess the possible anti-cancer effects of tangeretin, a dietary flavonoid on human prostate cancer cells (DU145, PC3, LNCaP). Tangeretin (25, 50 and 100 µM) significantly inhibited cancer cell viability and induced DNA fragmentation and apoptosis by increasing caspase-3 and pro-apoptotic proteins (Bad and Bax) with reduced anti-apoptotic proteins (Bcl-2 and Bcl-xL) expressions. Significant inhibition of androgen receptor (AR) and prostate specific antigen (PSA) were seen. Dose-dependent inhibition in Notch signal was observed in expression of Notch 1 and Jagged 1 along with PI3/Akt/mTOR signalling pathway. The results suggest that tangeretin inhibited prostate cancer cell proliferation and induced apoptosis via inhibiting critical pathways in cancer development - AR signalling and PI3/Akt/mTOR - Notch signalling pathways.